Tracking microbial community shifts during recovery process in overloaded anaerobic digesters under biological and non-biological supplementation strategies. (November 2021) - Rhee, Chaeyoung; Park, Sung-Gwan; Kim, Dae Wook; Yu, Sung Il; Shin, Juhee; Hwang, Seokhwan; Shin, Seung Gu
Graphical abstract: Highlights: Six augmentation strategies were compared to counteract organic overloading in AD. Bioaugmentation with HPr-enriched cultures showed the most effective relief. 'One-shot' injection of the enrichment gave the most immediate response. Consecutive injections of less volume led to persistence of the key taxa. H2 -using methanogens and their syntrophic partners were key drivers of recovery. Abstract: Anaerobic digestion encounters operational instability due to fluctuations in organic loading. Propionic acid (HPr) is frequently accumulated due to its unfavorable reaction thermodynamics. Here, 'specific' bioaugmentation using HPr enrichment cultures (three different injection regimes of quantity and frequency) was compared with 'non-specific' bioaugmentation using anaerobic sludge, and with non-biological supplementation of magnetite or coenzyme M. The specific bioaugmentation treatments showed superior recovery responses during continuous feeding after a peak overload. A 'one-shot' bioaugmentation with enrichment showed the best remediation, with ~25% recovery time and >10% CH4 conversion efficiency compared to the control. Consecutive bioaugmentation showed evidence of increased stability of the introduced community. Families Synergistaceae, Syntrophobacteraceae, and Kosmotogaceae were likely responsible for HPr-oxidation, in potential syntrophy with Methanoculleus and Methanobacterium . The different supplementation strategies can be considered to reduce the effect of start-up or overload in anaerobic digesters based on the availability of supplementation resources.